Association between serum glucose potassium ratio and short- and long-term all-cause mortality in patients with sepsis admitted to the intensive care unit: a retrospective analysis based on the MIMIC-IV database - Lou, Jiaqi; Xiang, Ziyi; Zhu, Xiaoyu; Song, Jingyao; Cui, Shengyong; Li, Jiliang; Jin, Guoying; Huang, Neng; Fan, Youfen; Xu, Sida (Frontiers in Endocrinology, 2025)
BackgroundThe glucose potassium ratio (GPR) is emerging as a biomarker for predicting clinical outcomes in various conditions. However, its value in sepsis patients admitted to the intensive care unit (ICU) remains unclear. Prior studies have shown conflicting results, with some indicating GPR’s potential as an early warning indicator of metabolic decompensation in septic patients, while others found no significant association. The current study addresses these inconsistencies by conducting the first large-scale, systematic validation of GPR in ICU sepsis patients.MethodsThis retrospective cohort study used patient records from the MIMIC-IV database to examine outcomes in sepsis patients. The primary outcomes were hospital and ICU mortality at 30, 60, and 90 days. The correlation between GPR and these outcomes was evaluated using Kaplan-Meier survival analysis, Cox regression models, and restricted cubic spline (RCS) regression analysis. Sensitivity analyses, including Propensity Score Matching (PSM) and E-value Quantification and Subgroup analyses, were performed to assess the robustness of the findings.ResultsThe study included 9,108 patients with sepsis. Kaplan-Meier survival curves indicated progressively worsening survival probabilities from Q1 to Q4 for both hospital and ICU mortality across all time points. Cox analysis revealed that patients in the highest GPR quartile (Q4) had a significantly increased risk of mortality compared to those in the lowest quartile (Q1). A nonlinear relationship between GPR and mortality was identified, with a critical threshold at GPR=30. Subgroup analysis showed that the effect size and direction were consistent across different subgroups. Sensitivity analyses, including E-value quantification and propensity score matching, supported the robustness of our findings.ConclusionThis study demonstrates that higher GPR levels strongly predict increased short- and long-term mortality risk in ICU-admitted sepsis patients. The composite nature of GPR, reflecting both hyperglycemia and hypokalemia, offers incremental prognostic value beyond single metabolic parameter. A critical threshold effect was observed at GPR=30, where risk substantially increased. This consistent association across patient subgroups positions GPR as a promising biomarker for identifying high-risk sepsis patients, warranting prospective validation.